Review of the lumbar infusion test use in pediatric populations: state-of-the-art and future perspectives - Vojtěch Novák; Adéla Bubeníková; Petr Skalický; Arnošt Mládek; Václav Gerla; Afroditi Despina Lalou; Aleš Vlasák; Róbert Leško; Ondřej Bradáč (Fluids and Barriers of the CNS)
Abstract Background The lumbar infusion test (LIT) is a routine part of the diagnostic process of various CSF dynamics disorders in adults. However, it is rarely used in the paediatric population due to a lack of evidence substantiating its efficacy and overall indications. Methods Articles utilizing the LIT in a paediatric cohort (≤ 18 years) were included according to the PRISMA guidelines with the Newcastle-Ottawa Scale to assess the risk of bias. This review was registered at PROSPERO database under number: CRD42024625857. Results A total of 15 studies, yielding 441 patients, were included in the review. The most common indications for LIT were to predict shunt responsiveness in hydrocephalus and idiopathic intracranial hypertension (IIH). In IIH, the interaction between cerebrospinal fluid pressure (CSFp) and sagittal sinus pressure (SSp) may offer valuable diagnostic insights and present a novel assessment approach. The LIT is a validated tool, especially effective for predicting shunt responsiveness and detecting malfunctions in both IIH and hydrocephalus. Conclusions Data surrounding LIT usage in children is lacking and most studies are outdated. Caution is needed when interpreting resistance to outflow (Rout) due to potential overestimation, with more attention directed to CSFp and the pressure within the venous system coupling in IIH. Future studies should focus on standardizing LIT protocols across age groups with focusing more on signal characteristics rather than individual parameters and fostering interdisciplinary collaboration to optimize diagnostic accuracy.